COLD CHAMBER DIE CASTING OF ALUMINIUM ALLOY: A CASE STUDY (Journal of Mechanical Engineering, 2017)
In the present work cold chamber die casting solution of Al alloy has been investigated as a case study of industrial component (crankcase). The study presented in this paper is based upon Taguchi based model on dimensional accuracy in cold chamber die casting. The castings prepared at proposed parametric settings have been studied for functional validation of the parts, as per statistical control point of view. The result of study highlights significant improvement in dimensional accuracy (as regards to statistical process control isconcerned) at proposed parametric settings of cold chamber die casting process.